Middle Pleistocene to Holocene palaeoenvironmental evolution of the south-eastern Alpine foreland basin from multi-proxy analysis. (1st May 2021) - Marcolla, A.; Miola, A.; Mozzi, P.; Monegato, G.; Asioli, A.; Pini, R.; Stefani, C.
Abstract: The multidisciplinary analysis of two long sedimentary successions of continental and shallow marine deposits from the Venetian plain (NE Italy) provides new data on the stratigraphic architecture and the landscape evolution of the south-eastern Alpine foreland basin during the last 210–220 ka, with further evidences of a warm temperate phase older than MIS 8. We present and discuss a detailed multi-proxy data set from these successions (GER1 and CB cores). The results of stratigraphic, palynological and micropalaeontological analyses are cross-interpreted, showing the potentiality of building a composite section of two close continental successions within the same alluvial system, the Brenta megafan, with 15 km distance between cores along a downstream direction. The chronology of the upper part of the cores is supported by radiocarbon dating, showing the presence of Last Glacial Maximum (LGM) and post-LGM fluvial deposits. Lower down, the estimated chronology relies on the tight integration between palynostratigraphy and lithostratigraphy, on the recognition of main unconformities, as well as on the correlation with other regional biostratigraphic records and the Northern Hemisphere/global isotopic record. The only marine transgression recorded in the studied successions is attributed to the MIS 7.3 and represents the basal tiepoint for the correlation between the two cores. Below the MIS 7.3 transgressive marine surface there is a fluvial succession with weakly-developed palaeosoils and a poor pollen content suggesting cold climate (possibly MIS 8), that lies on top of a thick peat layer showing palynological evidence of a warm temperate climate. The occurrence of well-preserved Pterocarya and Carya pollen in the basal peat level (GER1 core) is compared to that of other pollen sequences in Europe, providing new insights for the chronological framing of the problematic last occurrence of these taxa in the southern alpine area. Whilst mixed temperate forest persisted throughout MIS 7c-7a, conifers spread during MIS 6. By this time, a glaciofluvial aggradation phase is recorded, highlighting the strong relationship between glacial maxima and alluvial aggradation in the Venetian plain. None of the drilling sites were reached by the Last Interglacial sea transgression. However, the Eemian forest signature is well recorded in CB core, and the following Early to Middle Würm stadial-interstadial sequence is clearly outlined thanks to the joint analysis of the two successions. Broad-leaved thermophilous forests disappeared at the end of the Early Würm and only Pinus and Betula persisted throughout the LGM, during which a chronologically well-constrained glaciofluvial aggradation occurred. The last depositional event corresponds to the post-LGM cut-and-fill of fluvial incised valleys in GER1 core, and to soil evolution and very thin burial by Brenta River fluvial deposits in CB core. The comparison between the results of this study with data of previous deep cores in the distal alluvial plain remarks an increasing long-term subsidence towards Venice area. Highlights: The last two glacial cycles are well recorded in Central Venetian plain (NE Italy). Thick alluvial aggradation phases correlate to glacial culminations in the Alps. MIS 7.3 transgression is recorded as proximal marine facies in C. Venetian plain. Continental conditions persisted in C. Venetian plain during MIS 5.5 sea highstand. Pterocarya is only present in sediments older than 220 ka.